Meningkatkan Partisipasi Peserta Didik melalui Pendekatan Culturally Responsive Teaching pada Pembelajaran Hortatory Exposition Text - Listiani, Listiani; Kamaruddin, Abdul; Mamar, Herni (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study aims to improve students’ active participation in learning Hortatory Exposition Text through the implementation of Culturally Responsive Teaching (CRT) in class XI IPA 1 SMA Negeri 1 Palu. The research employed Classroom Action Research (CAR) using Kemmis and McTaggart’s model, conducted in two cycles consisting of planning, acting, observing, and reflecting stages. The research instrument was an observation sheet containing five indicators of active participation, adapted from Suryosubroto and Sudjana. The results showed a significant increase in student participation from the pre-cycle (25%), cycle I (55%), to cycle II (85%). The findings indicate that CRT effectively creates contextual and empowering English learning by linking materials to students’ local culture. This study concludes that CRT can be an alternative strategy for English teachers to enhance students’ active participation and learning motivation.